Size Matters: Corruption Perceptions versus Corruption Experiences by Firms - Rajeev K. Goel; Ummad Mazhar; Rati Ram (Center for Economic Studies and ifo Institute (CESifo), 2021)
This study uses a large firm-level data set covering more than 80 countries to explore the effects of firm-size, city-size, and government-size on perceived and experienced corruption. Four points summarize our main findings, which seem instructive and new. First, there is a broad structural similarity in the major determinants of perceived and experienced corruption. Second, larger firms and larger government size lower corruption perceptions and experience. Third, larger cities raise corruption perceptions and experience. Fourth, when the sample is limited to large cities, the corruption-lowering effect of government size loses significance throughout, while firm size loses significance in experience regressions.
Keywords: K42; L25; 330; corruption perception; corruption experience; firm size; government size; city size; emerging economies